A reconfigurable scintillator-based small array facility for cosmic ray studies. (June 2020) - Riggi, F; La Rocca, P; Nicotra, D; Parasole, O; Pinto, C
Abstract: The first operational tests of a low-cost, reconfigurable mini-array for cosmic rays are here reported. Such facility is intended mainly as an educational tool for master and PhD students, to carry out quantitative investigations in cosmic ray physics. Each detection module is based on a small scintillator tile, optically coupled to a Wavelength Shifter (WLS) bar and a Silicon photomultiplier for light collection and readout. An Arduino MEGA board is used for trigger, data acquisition and storage. GPS time stamping of the events is also provided. The tests carried out with a set of 30 detection modules, spread over an area of about 50 m 2, are here reported. About 300k shower events were collected during a period of 13 days, with a trigger involving at least a three-fold coincidence between the modules. Individual rates of the modules, together with environmental data (pressure and temperature) were also measured along the acquisition period. Multiplicity distributions in stand-alone mode and in coincidence with an additional detector located some distance apart were extracted from the data. The dependence of the shower rate on the atmospheric pressure was also investigated.